Special Topics in Structural Dynamics & Experimental Techniques, Volume 5 Proceedings of the 39th IMAC, A Conference and Exposition on Structural Dynamics 2021 - Epp, David S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Dynamics of Coupled Structures, Volume 5: Proceedings of the 39th IMAC, A Conference and Exposition on Structural Dynamics, 2021, the fourth volume of nine from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of the Dynamics of Coupled Structures, including papers on: Methods for Dynamic Substructures Applications for Dynamic SubstructuresInterfaces & Substructuring Frequency Based Substructuring Transfer Path Analysis .
Chapter 1. A Comparative Study of Joint Modeling Methods and Analysis of Fasteners -- Chapter 2. Historical Perspective of the Development of Digital Twins -- Chapter 3. Distributed Home Labs at the Time of the Covid -- Chapter 4. Closed-Form Solutions for the Equations of Motion of the Heavy Symmetrical Top with One Point Fixed -- Chapter 5. Equations of Motion for the Vertical Rigid-Body Rotor: Linear and Non-Linear Cases -- Chapter 6. Vibration Control in Meta-Structures using Reinforcement Learning Technique -- Chapter 7. Using Steady-State Ultrasonic Direct-Part Measurements for Defect Detection in Additively Manufactured Metal Parts -- Chapter 8. Towards Developing Arrays of Active Artificial Hair Cells -- Chapter 9. Challenges Associated with In-Situ Calibration of Load Cells in Force Limited Vibration Testing.
Keywords: Statics; Buildings -- Design and construction; Atoms; Metrology; Dynamics; Nonlinear theories; Mechanics, Applied; Mechanical Statics and Structures; Building Construction and Design; Metrology and Fundamental Constants; Applied Dynamical Systems; Engineering Mechanics; Structural dynamics -- Congresses